SISTEMA DE MEDIÇÃO DO DESEMPENHO: UMA METODOLOGIA PARA IMPLEMENTAÇÃO - Kronenberg, Roland (2006)
This research evaluates and proposes the adaptation of a performance measurement system implementation methodology. In order to identify the strengths and weaknesses of the implementation methodology, two case studies were analyzed. Initially, the historical origins of the performance measurement and the environmental conditions in witch it was created are presented. Then a critical analysis of the theoretical framework was conducted, identifying some negative aspects of the performance measurement process and management by measures. Finally a specific case study is presented and the adapted implementation methodology is revealed. This methodology comprehends the knowledge obtained and the experience lived through the participatory research besides the analysis conducted during this research.